2021
DOI: 10.3389/fonc.2021.769305
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Immunotherapy in Colorectal Cancers: Where Do We Stand?

Abstract: Colorectal cancer (CRC) is the second leading cause of cancer death in the world. Immunotherapy using monoclonal antibodies, immune-checkpoint inhibitors, adoptive cell therapy, and cancer vaccines has raised great hopes for treating poor prognosis metastatic CRCs that are resistant to the conventional therapies. However, high inter-tumor and intra-tumor heterogeneity hinder the success of immunotherapy in CRC. Patients with a similar tumor phenotype respond differently to the same immunotherapy regimen. Mutat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 254 publications
0
9
0
Order By: Relevance
“…Carcinoembryonic antigen (CEA) and melanoma-associated antigen (MAGE) are the first TAAs ever identified and widely explored in the clinical trials of CRC vaccine (16). Other TAAs targeted for CRC treatment include mucin 1 (MUC-1), epidermal growth factor receptor (EGFR), vascular endothelial growth factor receptor 1 and 2 (VEGFR1, VEGFR2), transmembrane 4 superfamily member 5 protein (TM4SF5), survivin, mitotic centromere-associated kinesin (MCAK), guanylyl cyclase C (GUCY2C), and 5T4 (17)(18)(19)(20).…”
Section: Tumor-associated Antigenmentioning
confidence: 99%
“…Carcinoembryonic antigen (CEA) and melanoma-associated antigen (MAGE) are the first TAAs ever identified and widely explored in the clinical trials of CRC vaccine (16). Other TAAs targeted for CRC treatment include mucin 1 (MUC-1), epidermal growth factor receptor (EGFR), vascular endothelial growth factor receptor 1 and 2 (VEGFR1, VEGFR2), transmembrane 4 superfamily member 5 protein (TM4SF5), survivin, mitotic centromere-associated kinesin (MCAK), guanylyl cyclase C (GUCY2C), and 5T4 (17)(18)(19)(20).…”
Section: Tumor-associated Antigenmentioning
confidence: 99%
“…Immunotherapy is a novel treatment option against several types of tumors. Tumor immunotherapy induces an immune cell-mediated immune response through the neoantigen expressed on a broad range of tumors [84]. The success of tumor immunotherapy in achieving long-lasting antitumor responses has demonstrated that immune cells, mainly T cells, could be utilized to eliminate tumor cells [85].…”
Section: Immune Checkpoint Targeting Immunotherapiesmentioning
confidence: 99%
“…With recent developments in cancer immunotherapy, both hematological and solid tumors respond to this treatment. In the last decade, immunotherapy has become popular as an alternative to surgery, chemotherapy, and radiotherapy for treating various tumors ( 3 , 4 ).…”
Section: Introductionmentioning
confidence: 99%